Exploring the use of the writing portal to support ESL students' writing process - Noraini Said (2015)
Studies have shown positive outcomes and benefits of collaboration in the stages of the writing process which contribute to students' writing development, particularly the use of technology such as open software and Web 2.0 tools which supports the Personal Learning Environment (PLE) and social constructivism. The purpose of this study is to explore the use of The Writing Portal (1WP) as a platform for online collaboration by pre-service English as second language (ESL) teachers when they embark on the five-stage writing process to accomplish their written coursework. lWP was introduced to serve as an online collaborative learning tool to support students' writing needs and improve their writing experience. Therefore, the study strives to achieve two purposes: to produce the prototype of a dynamic TWP by employing the systematic instructional model of ADDIE, and to test TWP usability by exploring its use in an actual written coursework in relation to all stages of the writing process. In the design and development stages, social constructivism related concepts such as the PLE, collaborative learning, and web 2.0 were emphasized. The implementation stage took into account Rogers' Diffusion of Innovation theory to explain the process that explains the behaviors ofTlWP users. The evaluation stage comprised of formative evaluation, and summative evaluation to complement the data obtained throughout the reiterative stages of ADDIE. The participants in the study were 16 pre-service ESL teachers in a teacher education institute. The course lecturer also participated in the study in collaboration with the researcher to integrate TWP into the coursework. Other participants in the design process included instructional technology experts and subject matter experts since the study also captured the development of TWP. The pre-service teachers' writing experiences in the 12-week written coursework were studied through a qualitative case study design. Data was obtained from reflections, interviews, online discourses, feedback forms, content analysis of instructors' comments in writing drafts and log files from the portal. Data analysis mainly includes thematic analysis in most of the sources, and Soller's Collaborative Learning Conversation Skills Taxonomy (2001) was used to analyze users' interaction in TWP to find evidence of collaboration. Besides, students' writing drafts prior to the use of the portal, and after, were collected and analyzed to track any development which may be contributed by the portal. Their activities captured in TWP, and writing experiences were also compared. Positive results were seen in the evident use of TWP in all stages of the writing process, and students' improved writing experiences and perceptions after TWP use. TWP is therefore seen as a promising online writing support tool for future use. This study has the intention to highlight the significant roles and responsibilities of instructors as developers which are rarely captured in literature, and add to the body of knowledge on product development in ESL writing research.